ASSESSMENT OF PEDESTRIAN ACCESSIBILITY IN THE DISTRICTS OF TASHKENT - Pulatova Zulfiya; Sadikov Ibragim (European Science Publishing, 2024)
This article examines the issue of assessing pedestrian accessibility in the city districts, taking into account the street and road network. Isochrons were created for each district of Tashkent, a pedestrian accessibility index was determined for distances of 400, 800 and 1200 meters, these indicators were compared and, as a result, a cumulative graph was compiled for this indicator.
Keywords: Pedestrian, destination arrival, isochrons, pixels, centroid, destination arrival index.